WHAT COLLEAGUES WRITE (BASED ON XII CONGRESS OF RUSSIAN CHILDREN'S INFECTIONISTS) - T. V. Cherednychenko (Детские инфекции (Москва), 2015)
An overview of research papers submitted for the XII Congress of Russian children's infectionists is provided. The Congress will be held 11—13 of December2013 inMoscow.